A multi-religious consensus on the ethics of sustainable development: Reflections of the Ethics in Action initiative - Anthony M. Annett; Jeffrey Sachs; Marcelo Sánchez Sorondo; William F. Vendley (Kiel Institute for the World Economy (IfW), 2017)
The challenges of sustainable development are primarily ethical in nature. Guided by a ceaseless quest for profit, today's global economy is synonymous with vast amounts of exclusion, indignity, and environmental devastation. To succeed, therefore, the Sustainable Development Goals require "moral capacity" as much as financial or technical capacity. In line with the recently-formed Ethics in Action initiative, the authors therefore propose a sequence of measures designed to better orient the global economy toward the common good, coherent with the values of the world's major religious traditions. These proposals are in the areas of financing, the pursuit of justice, and pedagogy.
Keywords: A13; F63; I30; O19; Z12; 330; ethics; sustainable development; religion; poverty